English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve the differentials by laplace transform
x''''(t) + x'''(t) = cos (t)
x(0) = x'(0) = x'''(0) = 0 x'' (0)=1

So i haven't covered laplace transforms in about 2 years and what i remember was the teacher saying "it wasn't on the final, so we won't cover it."
Need to know it now, and current prof expects us to already know it.....only went over what to do after we transform.

This is what i did.
S^4 x(s) - s^3 x(0) - s^2 x ' (0) - s x''(0) - x'''(0) +
s^3 x(s) - s^2 x(0) - s x'(0) - x''(0) = s^2 / (s^2 + 1)

Sub in the boundy conditions and solve for x(s). Is this correct so far?

thanks in advance

2007-01-28 12:54:24 · 2 answers · asked by My name is not bruce 7 in Science & Mathematics Mathematics

Not asking you guys to solve, just writing the problem statement exactly how it appeared.

Just if i'm doing it right.

2007-01-28 13:00:44 · update #1

2 answers

Yes, this is correct so far, though usually we distinguish between the function of s and the function of t by writing x(t) and X(s). So you should have
s^4 X(s) - s^3 x(0) - s^2 x'(0) - s x''(0) - x'''(0) + s^3 X(s) - s^2 x(0) - s x'(0) - x''(0) = s^2 / (s^2 + 1)
i.e.
s^4 X(s) - s + s^3 X(s) - 1 = s^2 / (s^2 + 1)

Good luck with the rest of it!

2007-01-28 13:41:35 · answer #1 · answered by Scarlet Manuka 7 · 0 0

♠ laplace or not laplace, I’d better lower the range first;
♣ x’’’ +x’’ =sint +C; 0+1=0+C; thus x’’’ +x’’ =sint +1;
♦ x’’ +x’ =-cost +t +C; 1+0=-1+0+C; thus x’’ +x’ =-cost +t+2;
♥ x’ +x=-sint +0.5t^2 +2t +C; 0+0=0+0+0+C; thus x’ +x=-sint +0.5t^2 +2t;
▲ and here is a real problem: we are lucky to do this x’+x=0; and here comes laplace: k+1=0, k=-1; thus x=u*exp(-t), u being integration constant to be varied; now return to ♥; x’ +x=-sint +0.5t^2 +2t;
or u’exp(-t) –u·exp(-t) +u·exp(-t) = -sint +0.5t^2 +2t; or u’ =exp(t)·(-sint +0.5t^2 +2t);
▼integrating by parts: u= (0.5(cost -sint) +0.5t^2 +t –1)·exp(t)+C;
x=0.5(cost -sint) +0.5t^2 +t –1 +C*exp(-t); 0=0.5-1+C; thus
x=0.5(cost -sint) +0.5t^2 +t –1 +0.5exp(-t);

2007-01-28 23:54:24 · answer #2 · answered by Anonymous · 0 0

fedest.com, questions and answers